Teacher Candidates’ Socialization Process: A Grounded Theory Study - Köybaşı, Fatma; Uğurlu, Celal Teyyar (Asian Journal of Education and Training, 2019)
The purpose of this research is to reveal teacher candidates’ experiences from the beginning of their service until being a teacher. In this study, the grounded theory research design was preferred. The study group was determined with criterion sampling. Based on the criterion that the participants have just completed the one-year candidacy process, 12 teachers from different branches participated in this research. Interview technique was used as a data collection tool. The data were collected through a semi-structured interview form. According to the result of the model, teacher candidates have emotional responses regarding their prospective professional life before starting such as excitement or nervousness. The first stage is called the adaptation process. The second stage indicates that the implementation stage is associated with the experiences in the adaptation. As for the third phase, experience-gaining, the teachers who could identify and improve the shortcomings in the implementation process, gained experiences.